Đàm thoại tiếng Anh hàng ngày. Tập 2 - Carney, Toney (Tổng hợp TP.HCM, 2011)
First time Introductions Everyday Greetings Telephone Greetings and Invitations Asking for and Giving directions Returning from the Supermarket Refusals and Excuses Planning the Vocation Going to visit Sue's Mother Packing your bags At the Doctor I am so sorry Sleeping late At the Airport At the Hotel At the Chinese Restaurant Congratulations Thank you